2009
DOI: 10.3201/eid1507.080410
|View full text |Cite
|
Sign up to set email alerts
|

Latent Tuberculosis and Active Tuberculosis Disease Rates among the Homeless, New York, New York, USA, 1992–2006

Abstract: We conducted a retrospective study to examine trends in latent tuberculosis infection (LTBI) and TB disease rates among homeless persons in shelters in New York, NY, 1992–2006. Although TB case rates fell from 1,502/100,000 population to 0, a 31% LTBI rate in 2006 shows the value of identifying and treating TB in the homeless.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 5 publications
0
23
1
3
Order By: Relevance
“…The prevalence of active TB as well as LTBI in our study was higher than that reported in New York in the US (31% of LTBI) [10] and in the Airin district in Japan (1.5% and 50.6% rate of active TB and LTBI, respectively) [9]. The higher rate of active TB and LTBI among homeless people in Seoul reflects the higher prevalence of active TB in South Korea (115 per 100 000 persons) compared with the US (4.7 per 100 000 persons) and Japan (27 per 100 000 persons) in 2009 [1].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The prevalence of active TB as well as LTBI in our study was higher than that reported in New York in the US (31% of LTBI) [10] and in the Airin district in Japan (1.5% and 50.6% rate of active TB and LTBI, respectively) [9]. The higher rate of active TB and LTBI among homeless people in Seoul reflects the higher prevalence of active TB in South Korea (115 per 100 000 persons) compared with the US (4.7 per 100 000 persons) and Japan (27 per 100 000 persons) in 2009 [1].…”
Section: Discussioncontrasting
confidence: 72%
“…Studies suggest that the majority of urban homeless TB cases are attributable to ongoing transmission of TB in developing countries, and recommendations call for tailored programs to address TB in these high-risk groups [6]. However, although several studies [5,7-10] have reported the prevalence rate of TB among homeless people, prior studies rarely compared the prevalence rates of both active and latent TB infection among homeless people to that of a control group or the general population. Rather, there is a report showing no statistically significant difference in pulmonary TB between homeless people and general population [11].…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 16%-31% of the PEH population in the United States has LTBI (12)(13)(14). During the 2016 shelter contact investigation, in which 180 contacts of smear-positive case-patients were identified, HCPH found a positivity rate of 23%.…”
Section: Resultsmentioning
confidence: 99%
“…As in most low-incidence countries, TB is concentrated in specific groups-mainly Indigenous populations and migrants from endemic countries. However, outbreaks have been reported in Vancouver, Toronto, Edmonton and Ottawa as well as in several US cities, typically among groups with overlapping risk factors, such as HIV/AIDS coinfection, homelessness, substance use and incarceration (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). While data on incidence rates of active TB in these groups are scarce, an incidence of 13.2/100,000 person-year has been reported among the homeless in Montréal (7).…”
Section: Introductionmentioning
confidence: 99%